De matéria a afeto: a construção do significado da joia - Passos, Ana Cristina Barral Mariani (2018)
This thesis seeks to understand the meaning of jewellery and how it is built in contemporaneity. The aim is to understand its relevance as a cultural object today and to present some particularities leading to its meaning in the Brazilian context. It is a kaleidoscope of small fragments built from the point of view of those who are present at any given point of the jewelry’s life cycle, especially in those moments when it seems to receive a greater load of meaning. The interlocutors, divided into creators, guardians and resignifiers, point out how the transition from matter to affection happens. This study is composed from small treasures revealed through reminiscences, memories and narratives of professional and personal histories, individual and collective ones, as well as some silences which occasionally accompany the pieces of jewelry. Design, creation, choice, acquisition, use, gift, inheritance, guard, collection, care, and discard of jewelry: all these interactions charge them with meanings and are also permeated by those meanings. The gesture of having pieces of jewelry on the body is ancient, but their meanings are not evident. They were captured in an ethnographic-inspired research from the microcosm of the researcher’s jewelry studio. Interviews, the studio’s archives, and an online survey made available on social networks were instrumental to identify that jewelry, bearer of affections, can make us beautiful and desirable, unique and special, protected and powerful. In a fast and increasingly volatile world, these characteristics seem to be essential to define us as individuals. Identity, memory and affection are at stake. The conclusion is that in a world of flourishing creative economics, a cultural artifact that retains much of the old ways of making-thinking is once again appreciated. In contemporary times, jewelry becomes a form of anchorage in a reality that is more virtual than concrete, more fleeting than perennial, more isolated than gregarious. Their meanings are grouped into three broad categories: the adornment of identity, the file of memory, and the treasure of affections. This object of study required an interdisciplinary approach. The anthropologist Tim Ingold (2015) and the philosopher Gilles Lipovetsky (2016) were chosen to outline the course of the investigation. The first suggested understanding ‘things’ as a mesh of matter and processes. The second presented the tools to perceive the contemporaneity. Authors of Cultural History, Material Culture and Social Memory were also important references. Jewelry theorists – a discipline still in its early stages – Marjan Unger (2017) and Liesbeth den Besten (2011) have given the compass to navigate this universe. It is the first who offered the definition of jewelry that pervades the whole thesis: “A piece of jewelry is a discrete object that is worn by human beings as a decorative and symbolic complement to their appearance.”